Continuous Renal Replacement Therapy with Regional Citrate Anticoagulation in Children with Liver Dysfunction/Failure. (23rd June 2022) - Botan, Edin; Durak, Ayşen; Gün, Emrah; Gurbanov, Anar; Balaban, Burak; Kahveci, Fevzi; Özen, Hasan; Uçmak, Hacer; Aycan, Fulden; Kendirli, Tanıl
Abstract: Regional citrate anticoagulation (RCA) is an option but citrate accumulation is risk and it is a giving up cause for this situation. This retrospective study was conducted in the pediatric intensive care unit (PICU) between May 2019 and April 2021. We investigated 47 patients with liver failure (LF) in our PICU, and RCA during continuous renal replacement therapy (CRRT) was applied to 10 (21.3%) of them. Half of them were male ( n : 5/10), their mean age was 104.7 ± 66.20 months. Nine of them needed vasoactive support during follow-up. The most common indication for CRRT was hepatorenal syndrome (40%). There was no significant difference between liver transaminases and liver function tests before and after CRRT ( p  > 0.05). In terms of citrate toxicity of the patients, there was no significant difference between total calcium/ionized calcium, lactate level, pH and bicarbonate values before and after CRRT ( p  > 0.05). The mean total CRRT time was 110.2 ± 118.2 h, and the mean circuit lifespan was 43.8 ± 48.7 h; the mean number of circuits was 2.7 ± 2.4. Total Ca/ionized Ca >2.5 was a clinically relevant endpoint, but no patient interrupted dialysis for this cause. There was no complication about RCA. This study did not observe any adverse effects on acid–base status, transaminases, an increase in bilirubin during RCA–CRRT treatment in pediatric patients with LF. Total calcium/ionized calcium ratio, serum lactate level and prothrombin time level should be closely monitored daily in terms of citrate accumulation in this patient group.